An Analysis Of Coherence And Cohesive Device In Writing Recount Text Used By The Fifth Semester Students Of English Department In HKBP Nommensen University - Nia Andriaty Manullang; Sahlan Tampubolon; Nurhayati Sitorus; Rina Octavia Simarmata (Universitas Pahlawan Tuanku Tambusai, 2023)
Coherence is characterized by the use of supporting details arranged in such a way that the information intended to be conveyed, and the frequent use of time and sequences to convey supporting information can appear at once. This study explains how the fifth-semester students' mastery of the types of cohesion and coherence in writing recount texts and the difficulties faced by students. The data obtained came from students' writing tests in recount texts and interview tests. This research is a qualitative descriptive study. In this study, 20 fifth-semester students of English education study programs. Data analysis was found in the form of the number of each type of cohesion and coherence from the students' writing test and using the answers to the interview test. In the results of the writing test in writing recount text, the writer found 946 uses of cohesion and coherence devices, divided into 568 services of references (60.04%), 11 substitutions (1.16%), 8 ellipses (0.84%), 237 conjunction (25.05%), repetition of 47 (4.96%), then there are synonyms with 14 uses (1.47%), 1 antonym (0.10%), keywords repeated with as many as 21 uses (2.21%), 11 pronoun references (1.16%), 14 signs/transition words (1.47%), and logical ideas (1.47%). Based on student interview papers, 10 students faced problems. There are 3 votes for each type of grammatical cohesion, 2 for each type of lexical cohesion and 5 for each type of coherence, 2 for grammar, 1 for vocabulary, and 2 for constructing story ideas. Cohesion is a type of problem that students rarely complain about, while coherence is the type of problem most often complained about by students.